2020
DOI: 10.1016/j.thromres.2020.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism and bleeding in critically ill COVID-19 patients treated with higher than standard low molecular weight heparin doses and aspirin: A call to action

Abstract: Background Critically ill COVID-19 patients have a clear pattern of inflammation and hypercoagulable state. The main aim of the study was to evaluate the outcome of severe COVID-19 patients basing on prothrombotic risk factors (i.e. D-dimer). We also evaluated the impact of different doses of low molecular weight heparin (LMWH) on the incidence of bleedings. Methods The data of forty-two patients admitted to the Intensive Care Unit (ICU) were retrospectively analyzed. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 25 publications
1
55
1
Order By: Relevance
“…Coagulopathy and blood clots are a significant adverse event in patients with COVID-19. Aspirin inhibits the coagulation due to its effect on platelets and has been reported to improve patient prognosis (3)(4)(5). The present study was not able to confirm this observation as the patients on aspirin in the current sample were significantly older and therefore less likely to survive.…”
Section: Discussioncontrasting
confidence: 66%
“…Coagulopathy and blood clots are a significant adverse event in patients with COVID-19. Aspirin inhibits the coagulation due to its effect on platelets and has been reported to improve patient prognosis (3)(4)(5). The present study was not able to confirm this observation as the patients on aspirin in the current sample were significantly older and therefore less likely to survive.…”
Section: Discussioncontrasting
confidence: 66%
“…Hence, early anticoagulation such as heparin may reduce coagulopathy, microthrombus formation, and the risk of organ damage. The role of heparin in COVID-19 is supported by several retrospective studies ( 84-86 ), but its exact curative effect and appropriate effective dose should be proven in high-quality clinical trials.…”
Section: Reviewmentioning
confidence: 99%
“…A recent retrospective observational study, evaluating the impact of different doses of LMWH on the incidence of bleedings in COVID-19 patients admitted to ICUs, showed that the use of therapeutic doses of heparin did not increase the risk of bleeding in their patient population. Moreover, the study suggested the importance of applying a risk stratification based on D-dimer values for critically ill patients with COVID-19 (Pavoni et al, 2020). Based on these considerations, a close clinical monitoring and an individual patient evaluation for the risk of thrombosis and bleedings should be applied (Gozzo et al, 2020).…”
Section: Anticoagulant and Antiplatelet Drugsmentioning
confidence: 99%